Use of PdCu catalysts supported on zirconia-ceria based supports for the elimination of oxyanions present in water - Navas, Marisa Belén (2021)
In the present work, the elimination of NO3-, NO2- and BrO3- in distilled and groundwater samples using H2 as reducing agent is studied. For this purpose, PdCu-based catalysts were prepared on CeO2 pure and modified with 10 % of ZrO2 supports. The prepared catalysts were characterized by N2 physisorption, SEM-EDS, XRD, TPR, RAMAN, FTIR and XPS. The results showed that the materials obtained were mesoporous, exposing the cubic CeO2 crystalline phase. Raman and FTIR analysis allow corroborating that both supports have oxygen vacancies, being higher in the ZrCe support, due to the presence of Zr4+ ions in the CeO2 lattice. All the prepared catalysts were active in the elimination of the selected oxyanions, showing high selectivities (>99 %) towards the product of interest (N2 and Br−), especially the catalyst PdCu/10ZrCe. This catalyst presented the highest oxyanion removal rate, which is higher for NO3− elimination (V0,NO3-: 5.6; V0,BrO3-:.0.93). In the reduction stage, Ce4+ is reduced to Ce3+, generating oxygen vacancies at the metal-support interface. It is postulated that the reduction of the anions occurs by interaction of the oxygen atoms of the NO3−, NO2− or BrO3− species with the oxygen-vacant sites generated. The addition of Zr on ceria support increases its ability to activate anions and reduce them. PdCu/10ZrCe catalyst was also tested using groundwater. The conversion results obtained were promising, 60 % for NO2−, 70 % for NO3− and 27 % for BrO3−.